The hermeneutic side of responsible research and innovation - Grunwald, Armin (London, UK : ISTE, Ltd. ; Hoboken, NJ : Wiley, 2016)
The book investigates the meaning of RRI if little or no valid knowledge about consequences of innovation and technology is available. It proposes a hermeneutical turn to investigate narratives about possible futures with respect to their contemporary meaning instead of regarding them as anticipations of the future.
5.2.3. Philosophical characterizations5.3. Defining nanotechnology: a mission impossible?; 5.4. The meaning of nanotechnology: the shift from a revolutionary to a quite normal technology; 5.4.1. Looking back: the development of nanotechnology's meaning; 5.4.2. Hermeneutic work on nanotechnology; 5.4.3. Lessons learned for RRI debates; 6. Robots: Challenge to the Self-Understanding of Humans; 6.1. Autonomous technology: challenges to our comprehension; 6.2. Robots that can make plans and Man's self-image; 6.2.1. Planning robots; 6.2.2. Planning as special type of acting.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Research -- Moral and ethical aspects; Technological innovations -- Moral and ethical aspects; Recherche -- Aspect moral; Innovations -- Aspect moral; BUSINESS & ECONOMICS -- Business Ethics; Research -- Moral and ethical aspects; Technological innovations -- Moral and ethical aspects